(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The purpose of this article is to carry out a theoretical study, consisting of an inventory and descriptive methodology of the doctrinal production on the applicability of the principle of special protection for the family in the context of tax law. Initially, an analysis will be made of the process of constitutionalization and the formation of a new concept of the family, as well as the influence of Robert Alexy’s fundamental rights theory and Niklas Luhmann’s systems theory on tax law, especially in relation to the constitutional rules that govern the national tax system. The study of the decisions of the German Constitutional Court carried out by jurist Humberto Ávila, which correlates the principles of the dignified guarantee of the human person and the special protection of families, will serve as an important guide in view of the constitutional limitations on the state’s power to tax. The principles of ability to pay and equality will also be dealt with in this article, from the perspective of their objective and subjective dimensions, with the primary aim of protecting family members from excessive and unreasonable conduct practiced by the state in the exercise of its taxing activity. The extrafiscality of taxation, qualified as a behavior-inducing norm, will be developed in the light of the principle of special protection for the family as an instrument to encourage the constitution, development and maintenance of the various types of families (marriage, stable union, same-sex union, single-parent family and socio-affective family). Finally, based on a constitutional concept of income, we will try to outline the field of taxation of the minimum necessary for the dignified existence of family members.